From the Workshop of the Mesopotamian Scribe : Literary and Scholarly Texts from the Old Babylonian Period - Klein, Jacob; Sefati, Yitschak (Book collections on Project MUSE., 2022)
This volume presents first editions of a variety of cuneiform tablets from the Old Babylonian period belonging to the collection of the late Shlomo Moussaieff. It makes available for the first time three texts representing varying levels of Mesopotamian scribal education. The first is what the authors argue is the most complete copy of the first fifty lines of the standard version of the Sumerian epic Gilgameš and the Bull of Heaven. The second is a hitherto unpublished bilingual (Sumerian-Akkadian) lexical list of unknown provenance, similar to the Proto-Aa syllabary. Each of the 314 entries preserved on this tablet provides a pronunciation gloss, a Sumerian logogram, and an Akkadian translation. A unique feature of this list is that the signs are arranged on the basis of graphic concatenation: each sign contains one of the graphic components of the preceding sign. It also yields a great number of hitherto unknown, synonymous Akkadian translations to the Sumerian logograms. The final chapter contains an edition of two groups of lenticular school tablets, containing thirty-three elementary-level scribal exercises.With this volume, Jacob Klein and Yitschak Sefati preserve and disseminate important artifacts that advance the study of Sumerian literature, Mesopotamian lexicography, and ancient Near Eastern scribal education.